A new species of Striga section Polypleurae (Orobanchaceae) from southern Western Ghats of India - Prabhu Kumar, K. M.; Omalsree, M.; Sabu, M.; Sunojkumar, P.; Thomas, Binu; Rajendran, A.; Sreenivas, V. K. (Phytotaxa, 2015)
A new species of Striga from Tamil Nadu parts of Western Ghats of India is described and illustrated as Striga kamalii sp. nov. The new species shows similarity with S. densiflora in having a densely hispid stem, linear leaves, bracts longer than calyx, and oblong fruit shorter than calyx lobes, but differs in the 10-ribbed calyx, the glandular hairs on calyx and corolla tube, and the obovate-rounded petals. A detailed description, with data on distribution and parasitism together with relevant taxonomic notes and colour photographs are provided.